2017
DOI: 10.1103/physrevx.7.021004
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics of Computational Copying in Biochemical Systems

Abstract: Living cells use readout molecules to record the state of receptor proteins, similar to measurements or copies in typical computational devices. But is this analogy rigorous? Can cells be optimally efficient, and if not, why?We show that, as in computation, a canonical biochemical readout network generates correlations; extracting no work from these correlations sets a lower bound on dissipation. For general input, the biochemical network cannot reach this bound, even with arbitrarily slow reactions or weak th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
137
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 86 publications
(140 citation statements)
references
References 63 publications
3
137
0
Order By: Relevance
“…For example, we saw that a naive version of Protocol 1 was intrinsically irreversible and therefore unable to reach the ultimate thermodynamic bounds based on starting and ending states. In recently published work [69], Ouldridge et al argue that realistic biochemical networks similarly cannot reach these fundamental bounds. In that case, the authors trace the extra dissipation to a failure to exploit all correlations generated between the measuring device and the physical system (receptors and readouts).…”
Section: Discussionmentioning
confidence: 99%
“…For example, we saw that a naive version of Protocol 1 was intrinsically irreversible and therefore unable to reach the ultimate thermodynamic bounds based on starting and ending states. In recently published work [69], Ouldridge et al argue that realistic biochemical networks similarly cannot reach these fundamental bounds. In that case, the authors trace the extra dissipation to a failure to exploit all correlations generated between the measuring device and the physical system (receptors and readouts).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, erasure in asymmetric states can be interpreted as situations where the initial system is out of global thermodynamic equilibrium. Since nonequilibrium settings are ubiquitous in biological systems, it is important to establish basic scenarios in simpler settings to understand more clearly, for example, why common biological systems may not be able to reach ultimate thermodynamic limits [26].…”
mentioning
confidence: 99%
“…Horowitz and Esposito showed that entropy production within a system X can be negative if X is coupled to a second system Y , and transitions in X decrease I(X; Y ) [18]. A third key result, essential to exorcising Maxwell's Demon [6,21], is that if X and Y are uncoupled from each other, yet coupled to heat baths at temperature T , then the total free energy is [22,23] HereF (X) = F eq (X) − kT x∈X p(x) ln(p eq (x)/p(x)) is the non-equilibrium free energy [20,23], with the tilde indicating the generalisation from the standard equilibrium free energy F eq (X). Systems X and Y could be two non-interacting spins, or two physically separated molecules.…”
mentioning
confidence: 99%